2017
DOI: 10.1007/s40519-017-0370-4
|View full text |Cite
|
Sign up to set email alerts
|

Is snack consumption associated with meal skipping in children and adolescents? The CASPIAN-IV study

Abstract: Meal skipping and snack consumption were frequent among Iranian children and adolescents. Evidence based interventions are proposed to improve the students' eating habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 55 publications
1
18
1
3
Order By: Relevance
“…The main results found in studies [15][16][17]20 that looked at replacing main meals with snacks were similar to previous studies, [49][50][51] whose replacement prevalence was higher at dinner and the main foods reported were energy-dense and nutrient-poor snacks. In addition to breakfast cereal, salad, yogurt, fruit and juice.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The main results found in studies [15][16][17]20 that looked at replacing main meals with snacks were similar to previous studies, [49][50][51] whose replacement prevalence was higher at dinner and the main foods reported were energy-dense and nutrient-poor snacks. In addition to breakfast cereal, salad, yogurt, fruit and juice.…”
Section: Discussionsupporting
confidence: 85%
“…Kelishadi et al 49 also found associations between leisure-time snacking and demonstrated that eating different types of junk food increased the chance of missing meals. Teixeira et al 51 described in their study that dinner was the most substituted meal, and consumed snacks had high energy density and low nutritional value.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Childhood excess weight increases the risk of obesity or overweight in the later years [7]. Shifts in dietary pattern can have significant effects on weight changes in terms of excess weight in children and adolescents [8,9]. Longitudinal studies have shown that there is an association between dietary patterns and cardiovascular diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted so far to identify and modify factors affecting breakfast and snack consumption behaviors [15][16][17]. Although they provided valuable information about these factors, they failed to identify the factors which market these behaviors.…”
Section: Introductionmentioning
confidence: 99%